EFEKTIVITAS VARIASI KONSENTRASI TEPUNG TALAS SEBAGAI MEDIA ALTERNATIF PERTUMBUHAN JAMUR Candida albicans - Marchamtia Sarah Nur Awalia Fajari; Muhammad Taufiq Qurrohman (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Taro flour (Colocasia esculenta (L.) Schott) has 77%% carbohydrate. A high carbohydrate source has the potential to be used as an alternative media in supporting the examination of Candida albicans fungal culture. Candida albicans is one of the fungi causing candidiasis. Therefore, this study aims to see the effectiveness of the variations of taro flour concentrations as an alternative media to the growth of fungus Candida albicans. The type of the study was experimental with a post test only control group design. The subjects of the study were taro flour media with concentrations of 0,12%, 0,24%, and 0,36% tested on fungus Candida albicans, which was inoculated by spread plate with PDA (Potato Dextrose Agar) media used as control. The data collection was performed by calculating the colony of Candida albicans, which grew in each media. The mean colony of each media on PDA, taro flour 0,12%, 0,24%, 0,36% were 15.5 colonies, 18.8 colonies, 19.5 colonies, and 20.8 colonies, respectively. The effectiveness test showed that all taro flour concentrations have a percentage more than 100%. The variation of taro flour has the growth effect of fungus Candida albicans. Thus, the higher the concentration of taro flour media, the more colony the number of Candida albicans grew. The effectiveness test showed that all taro flour concentrations was classified as very effective.